Matlab-Based Modeling and Simulation of Temperature and Pressure Parameter Settings for Geothermal Power Plants - Siagian, Parlin; Alam, Hermansyah; Putra, Randi Rian; Tanjung, Munawir Sajali (Cattleya Darmaya Fortuna, 2024)
This research focuses on modeling and simulating temperature and pressure parameter settings in geothermal power plants using MATLAB software. Geothermal power plants utilize geothermal heat as an energy source to produce electricity, so controlling temperature and pressure parameters is a key factor in optimizing system performance. The method used in this research includes developing a mathematical model of a geothermal power generation system, followed by numerical simulations to evaluate the dynamic response to variations in operational parameters. Simulation results show that proper regulation of temperature and pressure can increase plant efficiency and operational stability. In addition, this study also explores the influence of various parameter setting scenarios on the power output and energy consumption of the system. Implementation of the model in MATLAB makes it easy to visualize and analyze data, and allows real-time simulations needed for fast and accurate decision making. In conclusion, this research succeeded in showing that modeling and simulation using MATLAB is an effective tool for optimizing temperature and pressure parameter settings in geothermal power plants, which in turn can increase overall system efficiency and reliability.